Monitoring Atrial Fibrillation After Catheter Ablation - Forleo, Giovanni B (J Atr Fibrillation, 2014)
Although catheter ablation is an effective treatment for recurrent atrial fibrillation (AF), there is no consensus on the definition of success or follow-up strategies. Symptoms are the major motivation for undergoing catheter ablation in patients with AF, however it is well known that reliance on perception of AF by patients after AF ablation results in an underestimation of recurrence of the arrhythmia. Because symptoms of AF occurrence may be misleading, a reliable assessment of rhythm outcome is essential for the definition of success in both clinical care and research trials. Continuous rhythm monitoring over long periods of time is superior to intermittent recording using external monitors to detect the presence of AF episodes and to quantify the AF burden. Today, new devices implanted subcutaneously using a minimally invasive technique have been developed for continuous AF monitoring. Implantable devices keep detailed information about arrhythmia recurrences and might allow identification of very brief episodes of AF, the significance of which is still uncertain. In particular, it is not known whether there is any critical value of daily AF burden that has a prognostic significance. This issue remains an area of active discussion, debate and investigation. Further investigation is required to determine if continuous AF monitoring with implantable devices is effective in reducing stroke risk and facilitating maintenance of sinus rhythm after AF ablation.